International financial integration - LUCEY, BRIAN MICHAEL (My University, 2009)
Institutions and institutional structures are boundary conditions for finance. Since the pioneering work of La Porta et al., 1998 R. La Porta, F. Lopez-de-Silanes, A. Shleifer and R.W. Vishny, Law and finance, Journal of Political Economy 106 (6) (1998), pp. 1113?1115.La Porta et al. (1998), economics and finance have begun to rediscover the importance of considering not just what the markets are doing but the settings within which these markets operate. At a macro-level we see increasing evidence of the importance of the design of institutions and in the wake of the 2007?2008 crash a renewed interest in the importance of institutional capture and independence. At a more micro-level the same crash has refocused discussion of whether or not some institutionally imposed ?speed bumps? on the free operation of the markets may be beneficial in the longer term.
PUBLISHED
Keywords: Economics